Analysis of a Doubly-Fed Induction Motor for Soft Start Operation based on Stator Flux Vector Control - Warachart Suwan‐ngam (ECTI Transactions on Electrical Engineering Electronics and Communications, 2024)
This paper aims at analysis of an operation of a doubly-fed induction motor (DFIM). The paper mainly focuses on the soft start method for the DFIM using the conventional topology that is normally used in the case of a doubly-induction generator (DFIG). Likewise, the details about reactive power control is also discussed. With the proposed method, the DFIM can start from zero to any speed by controlling the machine-side converter (MSC). The computer simulation is performed to a 5 kW wound rotor induction motor using PLECS software. The simulation results validate that the DFIM can operate from the rest to any speed while operating only under the conventional topology.
Keywords: Power Systems and Renewable Energy; Electric Motor Design and Analysis; Sensorless Control of Electric Motors